The role of generic cognitive skills: an empirical investigation into the association between generic and sport-specific cognitive skills and playing level in youth football - Reinhard, M. L.; Mann, D. L.; Höner, O. (Journal of Science and Medicine in Sport, 2025)
Objectives Tests of cognitive skills are increasingly used to identify talent in sports such as football, but there is so far little evidence to suggest that those tests are associated with sport-specific cognitive skills and performance. The aim of this study was to establish the degree to which tests of generic cognitive skills are associated with football-specific skill in youth football. Specifically, we (i) established the degree to which tests of generic cognitive skills are associated with sport-specific cognitive skills, and (ii) compared the associations between generic and sport-specific cognitive skills and the playing level of youth footballers.